Social and economic implications of restrictions on individual rights and freedoms - Brașoveanu, Florica (Eximia, 2023)
Restrictions on individual rights and freedoms may be justified by governments by the need to protect public safety and security. However, such restrictions can have negative implications for individual liberty and can restrict the fundamental rights of citizens, with a negative impact on social, economic and mental health. Governments must consider the impact of restrictions on society and individuals and strike a balance between protecting individual rights and freedoms and protecting public safety.